Optimization of water resource dispatching for Huanghua Port under uncertain water usage scenario - Fang, Yong; Wang, Yanjiao; Liu, Qiang; Luo, Kan; Liu, Zhonghua (The Science of the total environment, 2021)
In recent years, large-scale coal bulk cargo ports have been vigorously promoting the green and intelligent construction, it is an important problem for them to manage water resources scientifically and effectively to realize energy conservation and environmental protection under uncertain circumstances. Taking Huanghua Port of Shenhua Group in China as an example, firstly, through a systematic review of the water resource dispatching infrastructures and production operations, the four-level water resource dispatching framework of Huanghua Port was obtained. Secondly, an uncertain multi-objective programming model is constructed to comprehensively consider the cost of water purchase, the energy consumption of water diversion, and the uncertainty of water usage. Then, an algorithm is designed according to the characteristics of the model. Finally, the applicability and effectiveness of the water resource dispatching framework, optimization model, and solution algorithm are verified by the analysis of 8 typical production water scenarios. This study not only provides Huanghua Port with a water resource dispatching optimization solution but also provides a decision-making reference for the green and intelligent transformation and upgrading of other large-scale coal bulk ports. In this paper, the water resource dispatching schemes for the eight typical water usage scenarios of Huanghua Port are optimized based on the optimal programming model. It can be seen that the optimal water resource dispatching distribution is more even, which basically eliminates idle water transfer routes, reduces the water diversion energy consumption, and effectively alleviates the problem that some water transfer routes are vacant before optimized dispatch and the others are overloaded. This is because, during the dispatching process, the intermediate water storage units maximize the water buffering effect under the guarantee of proper water storage requirements, and effectively responds to fluctuations in water cost caused by fluctuations in water consumption. Therefore, it is further illustrated that the research scheme of this paper mainly achieves cost reduction and energy saving by adjusting the water diversion volume of each supply unit and the water resource dispatching path for the port under the condition of meeting the water demand of each water usage unit. [Display omitted] •Take Huanghua Port as an example to study the water resource dispatching in the construction of green intelligent port.•A multi-objective programming model of water cost and energy consumption is established considering the uncertain scenarios.•The multi-objective programming model is transformed into a single-objective programming model, with a solution algorithm.•The experimental results show that the optimal scheme can significantly reduce the water cost and energy consumption.•This study provides decision-making reference for the green intelligent port construction of Huanghua Port and other ports.